THE INFLUENCE OF SUSTAINABILITY REPORTING ON INVESTOR DECISIONS IN MANUFACTURING COMPANIES - Antoni Antoni (Adisam Publisher, 2025)
This research aims to analyze the influence of sustainability reporting on investor decisions in manufacturing companies listed on the Indonesia Stock Exchange (IDX). The research uses a quantitative approach with an explanatory method. The research population includes all manufacturing companies that publish sustainability reports, with sample selection done thru purposive sampling. The data used consists of secondary data in the form of annual reports and sustainability reports, as well as optional primary data from questionnaires or interviews with investors. The independent variable is sustainability reporting, measured using ESG (Environmental, Social, Governance) indicators, while the dependent variable is investor decisions. Data analysis techniques include validity and reliability testing, multiple linear regression analysis, and hypothesis testing (t-test, F-test, and coefficient of determination). The research findings indicate that sustainability reporting significantly impacts investor decisions, with environmental and governance aspects being the most dominant factors. Companies with high compliance levels with GRI or POJK standards tend to attract greater investor interest and achieve higher stock trading volumes. This finding confirms that sustainability reporting is not only a regulatory obligation, but also an effective business strategy for building trust and corporate reputation. The recommendations of this research encourage companies to improve the quality of their sustainability reporting, and for regulators to strengthen policies and oversight to create a healthy, transparent, and sustainable investment climate.